Exploring perceived walkability in one-way commercial streets: An application of 360° immersive videos. - Dao Chi Vo; Jeongseob Kim (PLoS ONE)
This study explores the perceived walkability of one-way commercial streets by utilizing immersive 360-degree virtual reality (VR) videos. While one-way roads are often introduced to facilitate smooth traffic flow on narrow roads, providing safe and walkable environments for pedestrians on the one-way roads is crucial, especially in commercial areas with heavy pedestrian traffic. We recruited 40 students to assess the perceived walkability of one-way roads based on ten VR scenarios. For each scenario, variables such as road width, one-way traffic status, vehicle approach direction, and the presence of sidewalks were configured differently. This study found that while there is awareness of one-way road types, the presence of sidewalks is considered critical factor contributing to enhanced perceived walkability on narrow commercial street. In the condition of narrow road width, one-way roads are the only applicable road layout to have a sidewalk, implying the potential of one-way roads for better walkability. Besides, the study also revealed the high correlation between five dimensions of perceived walkability, emphasizing their role to enhance perceived walkability in a setting of one-way roads. This study's findings could be utilized for more systematic walkability assessments and urban design improvements, especially in constrained road spaces.